Identification of another member of the transforming growth factor type beta gene family. - ten Dijke, P (1988)
We report here the complete amino acid sequence of another member of the type beta transforming growth factor gene family, deduced from the nucleotide sequence of three overlapping cDNA clones. The C-terminal 112 amino acids share approximately 80% sequence identity with type beta 1 and beta 2 transforming growth factors, with many of the remaining differences being conservative substitutions. By analogy to type beta 1 and type beta 2 transforming growth factors, we predict the protein to be synthesized as a 412 amino acid precursor that undergoes proteolytic cleavage to produce the mature polypeptide.